Molecular mechanism of enhanced ethanol tolerance associated with hfq overexpression in Zymomonas mobilis - Tang, Ying; Wang, Yi; Yang, Qing; Zhang, Youpeng; Wu, Yalun; Yang, Yongfu; Mei, Meng; He, Mingxiong; Wang, Xia; Yang, Shihui (Frontiers in Bioengineering and Biotechnology, 2022)
Zymomonas mobilis is a promising microorganism for industrial bioethanol production. However, ethanol produced during fermentation is toxic to Z. mobilis and affects its growth and bioethanol production. Although several reports demonstrated that the RNA-binding protein Hfq in Z. mobilis contributes to the tolerance against multiple lignocellulosic hydrolysate inhibitors, the role of Hfq on ethanol tolerance has not been investigated. In this study, hfq in Z. mobilis was either deleted or overexpressed and their effects on cell growth and ethanol tolerance were examined. Our results demonstrated that hfq overexpression improved ethanol tolerance of Z. mobilis, which is probably due to energy saving by downregulating flagellar biosynthesis and heat stress response proteins, as well as reducing the reactive oxygen species induced by ethanol stress via upregulating the sulfate assimilation and cysteine biosynthesis. To explore proteins potentially interacted with Hfq, the TEV protease mediated Yeast Endoplasmic Reticulum Sequestration Screening system (YESS) was established in Z. mobilis. YESS results suggested that Hfq may modulate the cytoplasmic heat shock response by interacting with the heat shock proteins DnaK and DnaJ to deal with ethanol inhibition. This study thus not only revealed the underlying mechanism of enhanced ethanol tolerance by hfq overexpression, but also provided an alternative approach to investigate protein-protein interactions in Z. mobilis.